The Role of Autophagy and Related MicroRNAs in Inflammatory Bowel Disease - Shiyuan Wang; Yan Huang; Cili Zhou; Huangan Wu; Jimeng Zhao; Luyi Wu; Min Zhao; Fang Zhang; Huirong Liu (Gastroenterology Research and Practice)
Accumulating evidence demonstrates that microRNA- (miR-) mediated posttranscriptional regulation plays an important role in autophagy in inflammatory bowel disease (IBD), a disease that is difficult to manage clinically because of the associated chronic recurrent nonspecific inflammation. Research indicates that microRNAs regulate autophagy via different pathways, playing an important role in the IBD process and providing a new perspective for IBD research. Related studies have shown that miR-142-3p, miR-320, miR-192, and miR-122 target NOD2, an IBD-relevant autophagy gene, to modulate autophagy in IBD. miR-142-3p, miR-93, miR-106B, miR-30C, miR-130a, miR-346, and miR-20a regulate autophagy by targeting ATG16L1 through several different pathways. miR-196 can downregulate IRGM and suppress autophagy by inhibiting the accumulation of LC3II. During the endoplasmic reticulum stress response, miR-665, miR-375, and miR-150 modulate autophagy by regulating the unfolded protein response, which may play an important role in IBD intestinal fibrosis. Regarding autophagy-related pathways, miR-146b, miR-221-5p, miR-132, miR-223, miR-155, and miR-21 regulate NF-κB or mTOR signaling to induce or inhibit autophagy in intestinal cells by releasing anti- or proinflammatory factors, respectively.